Anisotropic magnetothermal resistance in Ni nanowires - Kimling, Johannes; Gooth, Johannes; Nielsch, Kornelius (Physical Review B - Condensed Matter and Materials Physics, 2013)
We present measurements of the electrical and thermal transport properties of individual Ni nanowires as a function of the applied magnetic field, recorded in the temperature range between 78 and 380 K. In analogy to the anisotropic magnetoresistance (AMR) effect observed in ferromagnetic conductors, we find that the thermal resistance of Ni nanowires depends on the angle between magnetization vector and current direction. This anisotropic magnetothermal resistance effect turns out to be weaker than the AMR effect in Ni nanowires over the temperature range investigated. As a consequence, also the Lorenz number is found to be anisotropic with respect to the magnetization direction. To explain our observation, we propose a simple model that considers spin mixing due to electron-magnon scattering. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20